Optimization of Stock Portfolio Using the Markowitz Model in the Era of the COVID-19 Pandemic - Aisha Hanif; Nur Ravita Hanun; Rizki Eka Febriansah (TIJAB (The International Journal of Applied Business), 2021)
Stocks are one of the popular investment instruments traded in the capital market. The popularity of stock purchase has developed along with the massive financial literacy movement. However, the massiveness of this movement must be balanced with knowledge and expertise in managing stock instruments since they have a high return rate and high risk. One way to manage stocks is by developing an optimal stock portfolio based on the Markowitz model. The Markowitz model is a method that formulates the elements of return and risk in an investment, and specifically the elements of risk can be minimized through diversification and combination of various investment instruments into a portfolio. By using the Markowitz method, investors can take advantage of all available information as a basis for maximizing the portfolio. This study aimed to determine which stocks can form an optimal portfolio, especially in the era of the COVID 19 pandemic and the optimal proportion of the portfolio that is feasible to obtain from stocks listed in the LQ 45 Index. The study samples involved stocks listed in the LQ 45 Index. The data analysis technique applied in this study was portfolio optimization using the Markowitz model. The results of this study showed that the optimal portfolio consisted of BBCA with a weight of 78.09% and BRPT with a weight of 21.91% which produced an expected return of 2.35% and a standard deviation of 7.01%.